Vesicle-Associated Membrane Protein 4 and Syntaxin 6 Interactions at the Chlamydial Inclusion - Kabeiseman, Emily J. (American Society for Microbiology, 2013)
The predominant players in membrane fusion events are the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) family of proteins. We hypothesize that SNARE proteins mediate fusion events at the chlamydial inclusion and are important for chlamydial lipid acquisition. We have previously demonstrated that trans-Golgi SNARE syntaxin 6 localizes to the chlamydial inclusion. To investigate the role of syntaxin 6 at the chlamydial inclusion, we examined the localization and function of another trans-Golgi SNARE and syntaxin 6-binding partner, vesicle-associated membrane protein 4 (VAMP4), at the chlamydial inclusion. In this study, we demonstrate that syntaxin 6 and VAMP4 colocalize to the chlamydial inclusion and interact at the chlamydial inclusion. Furthermore, in the absence of VAMP4, syntaxin 6 is not retained at the chlamydial inclusion. Small interfering RNA (siRNA) knockdown of VAMP4 inhibited chlamydial sphingomyelin acquisition, correlating with a log decrease in infectious progeny. VAMP4 retention at the inclusion was shown to be dependent on de novo chlamydial protein synthesis, but unlike syntaxin 6, VAMP4 recruitment is observed in a species-dependent manner. Notably, VAMP4 knockdown inhibits sphingomyelin trafficking only to inclusions in which it localizes. These data support the hypothesis that VAMP proteins play a central role in mediating eukaryotic vesicular interactions at the chlamydial inclusion and, thus, support chlamydial lipid acquisition and chlamydial development.